-5(y-5)=3y-7

Simple and best practice solution for -5(y-5)=3y-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(y-5)=3y-7 equation:


Simplifying
-5(y + -5) = 3y + -7

Reorder the terms:
-5(-5 + y) = 3y + -7
(-5 * -5 + y * -5) = 3y + -7
(25 + -5y) = 3y + -7

Reorder the terms:
25 + -5y = -7 + 3y

Solving
25 + -5y = -7 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
25 + -5y + -3y = -7 + 3y + -3y

Combine like terms: -5y + -3y = -8y
25 + -8y = -7 + 3y + -3y

Combine like terms: 3y + -3y = 0
25 + -8y = -7 + 0
25 + -8y = -7

Add '-25' to each side of the equation.
25 + -25 + -8y = -7 + -25

Combine like terms: 25 + -25 = 0
0 + -8y = -7 + -25
-8y = -7 + -25

Combine like terms: -7 + -25 = -32
-8y = -32

Divide each side by '-8'.
y = 4

Simplifying
y = 4

See similar equations:

| -3(4+6w)-4= | | -18-10x=-16x+18 | | 189-10x=3x+20 | | 3v+30=6(v+8) | | 19v+7=167-v | | 3(-9-x)=42 | | 5000=0.3x^4-7.2x^3+43.2x^2+131.2 | | 6x+5+3x-1= | | 7k+12=19k-12 | | 4x+2y=190 | | 3(-9+x)=-21 | | x/5=60/75 | | 3[6+2(4+2)-5]+4= | | -7(5x+2)=-84 | | 5(-9+5q)= | | 2(2+5x)=-106 | | 6x^2+20-7x=0 | | 7(3x+1)-2(2x+4)= | | 7(2x+6)=-84 | | -2(6-4x)=44 | | u/3-13=1 | | -7(-7-x)=35 | | Log(X)=120 | | y=-25x+25 | | -4(2+5x)=152 | | 7.29x+21.87=43.74 | | (8x-7)(3-x)=0 | | 24x-20+21-30x=15 | | 2(-5-6x)=-46 | | 7b+-15=5b+-3 | | 11-2*3/5=0 | | -8(u-1)=-4u+12 |

Equations solver categories